Review for a monograph Iryna Boryshkevych, Valentyna Yakubiv “Mechanism of Formation and Implementation of the Development Strategyof Agricultural Enterprises” - Hrynchutsky , Valery (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
Review for a monograph Iryna Boryshkevych, Valentyna Yakubiv “Mechanism of Formation and Implementation of the Development Strategyof Agricultural Enterprises”